Sports in American history from colonization to globalization - Gems, Gerald R.; Borish, Linda J. 1961-; Pfister, Gertrud 1945- (Champaign, IL Human Kinetics, 2017)
Sports in American History: From Colonization to Globalization, Second Edition, journeys from the early American past to the present to give students a compelling grasp of the evolution of American sporting practices. This text provides students with insights into new and alternative perspectives, examines sport as a social and cultural phenomenon, generates a better understanding of current sport practices, and considers future developments in American sport. The second edition includes the following enhancements: The final chapter highlights sport in the twenty-first century and gives students an updated view of contemporary sport; Content about the progressive era now makes up two chapters and provides students with a clearer understanding of this instrumental period; New "People and Places" and "International Perspectives" sidebars introduce key figures in sport history and provide students with a global understanding of sport; Time lines with major sport and societal events and milestones provide context in each chapter; More than 150 images provide historical authenticity and relate people and events to the accompanying text; Chapter objectives and discussion questions help students absorb and apply relevant content. This comprehensive resource delivers coverage of sport by historical periods--from the indigenous tribes of premodern America, through colonial societies, to the era of sport in the United States today. Sports in American History, Second Edition, examines how women, minorities, and ethnic and religious groups have influenced U.S. sporting culture. This gives students a broader knowledge of the complexities of sport, health, and play in the American experience and how historical factors, such as gender, ethnicity, race, and religion, provide a more complete understanding of sports in American history. The easy-to-follow material is divided into 11 chronological chapters starting with sporting practices in colonial America and ending with globalized sport today, making it ideal for a semester-long course. The second edition maintains dedication to providing authentic primary documents--including newspapers, illustrations, photographs, historical writings, quotations, and posters--to bring the time periods to life for students. An extensive bibliography features primary and secondary sources in American sport history. Sports in American History, Second Edition, is unique in its level of detail, broad time frame, and focus on sports and the evolving definitions of physical activity and games. In addition, excerpts from primary documents provide firsthand accounts that will not only inform and fascinate readers but also provide a well-rounded perspective on the historical development of American sport. With sidebars offering an international viewpoint, this book will help students understand how historical events have shaped sport differently in the United States than in other parts of the world.
Chapter 1. Sporting Experiences in Colonial America, 1400-1750 ; Native American Pastimes and Sports ; Influence of Religion on English Colonists ; Sport in American Colonies ; Summary -- Chapter 2. Sport and Pastimes in the American Revolutionary Era and Early National Period, 1750-1820 ; The Great Awakening and the Place of Sport ; Consumerism and Changing Patterns of Colonial Life ; The Enlightenment in America and Ideas of Sport and the Body ; Frontier and Backcountry Sport ; Women's Active Recreation in the Revolutionary Era and Early National Period ; Native American Sport ; Sporting Practices During the American Revolutionary War ; Turn of the Nineteenth Century and Societal Patterns ; Summary -- Chapter 3. Antebellum Health Reforms and Sporting Forms, 1820-1860 ; Overview of the Antebellum Period ; Health Reformers ; Muscular Christianity ; Women and Physical Activity ; Rural Sporting Practices ; Rise of Agricultural and Sporting Journalism ; Sporting Practices of the Middle and Upper Classes ; Public Spaces for Health and Sport ; Sporting Pastimes of African Americans and Native Americans ; Immigrants and Sporting Cultures ; Summary -- Chapter 4. Rise of Rationalized and Modern Sport, 1850-1870 ; Concept of Modern Sport ; Subcommunities and the Growth of Modern Sport ; Sporting Fraternity ; Growth of Sports Clubs and Advancing Rational Recreation ; Growth of American Team Sport and Competition ; Rise of Intercollegiate Sport ; The Civil War and Sporting Experiences ; Summary -- Chapter 5. New Identities and Expanding Modes of Sport in the Gilded Age, 1870-1890 ; Sport and Social Stratification ; Maintaining Ethnic Forms of Leisure ; Development of an Intercollegiate Sporting Culture ; Male Sporting Culture ; Business of Sport ; Gendered Sport, Class, and Social Roles ; Regulation of Sport: Amateurism Versus Professionalism ; Summary -- Chapter 6. American Sport and Social Change During the Early Progressive Era, 1890-1900 ; Social Reformers of the Progressive Era ; Play and Games in American Ideology ; Recreational Spaces ; Back-to-Nature Movement ; Ethnic Groups ; Body Culture ; Sport and Technology ; Modern Olympic Games ; Summary -- Chapter 7. Sport as Symbol: Acculturation and Imperialism, 1900-1920 ; Sport, Ethnicity, and the Quest for Social Mobility ; Assimilation of Disparate Groups in American Society ; Challenging Gender Boundaries ; Resistance to Social Reform ; Sport and Colonialism ; Sport During World War I ; Summary -- Chapter 8. Sport, Heroic Athletes, and Popular Culture, 1920-1950 ; War, Depression, and the Shaping of America ; Social Change and the Spread of Sport ; Heroes in the Golden Age ; Media and the Commercialization of Sport ; Summary -- Chapter 9. Sport as TV Spectacle, Big Business, and Political Site, 1950-1980 ; Sport in the Cold War ; Evolution of the Sport-Media Relationship ; Incorporation of Alternative Heroes ; Professional Sport and Labor Relations ; Sport and the Civil Rights Movement ; Sport, Narcissism, and the Existential Search for Self ; Scientific Advancements and the Growth of Sport ; Summary -- Chapter 10. Globalized Sport, 1980-2000 ; Corporate Sporting Culture ; Drawing Fans to Baseball ; Michael Jordan and the Growth of Professional Basketball ; Intercollegiate Sport and the NCAA ; Women and Sport ; Drug and Body Abuse Among Athletes ; Violence in Sport ; Discrimination at the End of the Twentieth Century ; Individuality and Sport Icons ; Alternative Sports ; Summary -- Chapter 11. Sport in the Early Twenty-First Century, 2000-2015 ; Business of Professional Sports Teams ; Intercollegiate Sport and Conference Changes ; Title IX and Sport Leadership ; Women's Professional Teams and Endorsements ; Modern Olympic Challenges and Stars ; Sporting Crises ; Traumatic Brain Injury ; X Games and Alternative Sports ; Youth Sports ; Rise of the Runner ; The Future of Sport ; Summary.
Includes bibliographical references
Also available in print format
Keywords: Sports -- United States -- History; Sports -- Social aspects -- United States -- History